Model-independent evidence for J/[psi]p contributions to [lambda]0b→J/[psi]pK- decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physical review letters, 2016)
The data sample of Λ0b→J/ψpK− decays acquired with the LHCb detector from 7 and 8 TeV pp collisions, corresponding to an integrated luminosity of 3 fb−1, is inspected for the presence of J/ψp or J/ψK− contributions with minimal assumptions about K−p contributions. It is demonstrated at more than nine standard deviations that Λ0b→J/ψpK− decays cannot be described with K−p contributions alone, and that J/ψp contributions play a dominant role in this incompatibility. These model-independent results support the previously obtained model-dependent evidence for P+c→J/ψp charmonium-pentaquark states in the same data sample.